Modeling Dynamic Economic Systems - Ruth, Matthias; Hannon, Bruce (Modeling Dynamic Systems,, 2012)
Economists model the ways in which humans meet their needs using given endowments of resources and technologies.  This book explores the dynamic processes in economic systems, concentrating on the extraction of resources that are required to meet economic needs. Using the STELLA® software, Modeling Dynamic Economic Systems applies methods of computer modeling to a wide range of real-world economic phenomena, demonstrating how to make informed decisions about economic performance and environmental quality.  Sections of the book cover: methods for dynamic modeling economics with special emphasis on the microeconomic models of firms, modeling optimal use of both nonrenewable and renewable resources, and chaos in economic models.  The book does not require a substantial background in mathematics or computer science and encourages all students and scholars to actively incorporate modeling into their education and research.  A save-disabled version of STELLA and the computer models of this book are available at www.iseesystems.com/modelingeconomicsystems.   About the Authors Matthias Ruth is Roy F. Weston Chair in Natural Economics at the University of Maryland, College Park. Bruce Hannon is Jubilee Professor (Emeritus) of Liberal Arts and Sciences at the University of Illinois, Urbana-Champaign.   About the Series The availability of powerful, intuitive software for developing and running computer models of real-world phenomena promises a revolution in studying, teaching and thinking about complex problems that range from the functioning of a cell to that of an ecosystem to that of a national economy.  The books in the series Modeling Dynamic Systems promote the spread of "systems thinking" by integrating state-of-the-art modeling techniques with the theories and concepts of specific disciplines or interdisciplinary topics.  The unifying theme of the series is the ease, power, and transparency of model building.